SISTEM INFORMASI AKUNTANSI DALAM MENUNJANG PENENTUAN HARGA POKOK PRODUKSI BERBASIS CLIENT SERVER - sri wahyuning (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2019)
Abstract Accounting information systems are needed by companies, because they help a lot, in the effectiveness and efficiency of business problems. Determination and calculation of cost of production is a very important thing to know the production costs incurred as well as the benefits to be obtained. PT. Barokah Sejahtera is a company engaged in wall paint products, where in its products depends on the policy of determining and calculating factory overhead costs, if factory overhead costs are the dominant cost, then allocation based on volume will cause errors in determining cost of production by calculating the overall cost raw materials issued with products produced during the production process. In addition, the process of recording and calculation requires considerable time which results in difficulties in analyzing profits. To overcome these problems, the application of Activity Based Costing System and Client Server based methods is carried out. All activities are intended to produce products with adequate costs. The main focus of company management on activity management, namely planning and controlling all company activities in producing products with the appropriate cost level. The research method used is the RND method / Reset and Development Accounting information system calculation of the cost of production is expected to be applied to the company so that it can be more effective and efficient in calculating the cost of production